Case Report: Radical Vulvectomy V-Y Flap Surgical Procedure in a Woman with Vulva Cancer - Dionisius Christian Bria Seran; Yahya Irwanto; Arif Satria Hardika (Asian Journal of Health Research, 2024)
Introduction: Vulva cancer is one of the relatively rare malignancies, accounting for only 4% of all malignancies in gynecologic organs. Vulva cancer is often asymptomatic. Surgery is the basic management in patients with earliest-stage vulvar cancer and frequently requires a combined radical vulvectomy followed by inguinal LN dissection through a separate incision. Therefore, the author hopes this case can add insight into the knowledge related to early detection and comprehensive management of vulva cancer. Case Presentation: A woman, 67 years old, referred from Gambiran General Hospital Kediri with a vaginal biopsy result of vulva cancer, came to the Saiful Anwar General Hospital oncology clinic. The patient complained of pain in the pubic area accompanied by tissue growth around the pubic area since August 2023. History of weight loss (+) 10 kg in the past year. History of menopause since 18 years ago. The examination results obtained vital signs: BP 132/79 mmHg, pulse 128x/min, RR 20x/min, temperature 36.5C, height 155 cm, weight 40kg, and BMI 16.64 kg / m2 (underweight). Physical examination of external genitalia revealed a 12x8 cm mass on the right vulva, odour (+). The results of the vulvar biopsy examination on 25/08/2023 were found to be squamous cell carcinoma, well differentiated. The patient is planned for elective-wide excision. The management performed was radical vulvectomy with V-Y flap reconstruction surgery. Conclusion: In this case, it can be concluded vulva cancer is a relatively rare malignancy. The subtype often found is SCC (90-95%). This patient planned for radical vulvectomy using the V-Y flap reconstruction technique with SAB.